Analysis Studi Bridge Simulator Bagi Taruna Taruni Pelayaran SMK N 1 Bukit Batu - Suzdayan; Zusniati; Embing Sukarriya (ABEC Indonesia, 2023)
This research aims to determine the level of satisfaction with the implementation of familiarization with the bridge simulator for Nautika Cadets at SMK Negeri 1 Bukit Batu in the Maritime Department. This research was carried out in the Maritime Department of the Bengkalis State Polytechnic within 1 month using primary data and secondary data. Primary data collection was carried out by distributing questionnaires directly to 22 familiarization participants. Meanwhile, secondary data collection was obtained from the internet, such as searching Google Scholar to access articles from various scientific journals. The hypothesis of this research is that familiarization using the bridge simulator is considered to increase cadets' knowledge and skills in navigation. This research uses descriptive analysis techniques. Descriptive analysis is used for qualitative data and is presented in tabulated form. The results obtained are then presented as a percentage based on the number of respondents. The results of research using Likert Scale analysis show that the satisfaction level index for the familiarization implementation indicator is at 60.9% which is in the very satisfied category, 60.5% for the familiarization material indicator which is in the very satisfied category, the familiarization media indicator is at the 69% category. very satisfied and the indicator of the instructor's ability to manage the class is at 65.2% in the very satisfied category. From these results it was concluded that the satisfaction level of participants familiarizing themselves with the bridge simulator with simulator practice was very satisfied at 91%.   Keywords: familiarization, bridge simulator, Nautical